Het standbeeld van Van Riebeeck, geschenk van Cecil John Rhodes, dat in 1899 in Kaapstad onthuld werd
Het standbeeld van Van Riebeeck, geschenk van Cecil John Rhodes, dat in 1899 in Kaapstad onthuld werd.